OLENA APANOVYCH AS A PRESERVER OF NATIONAL UKRAINIAN HISTORY HERITAGE - Oleksandr Bon; Svitlana Savchenko (Київські історичні студії)
Olena Mykhailivna Apanovych belonged to socially active Ukrainian historians. Being among that small group of non-conformists to the Soviet regime, she became famous both due to the cossacks history research, popularization of their history, and cultural heritage preservation. In independent Ukraine she concentrated on preservation work and made a significant impact on recovery of national idea. The aim of this research is to unveil Olena Apanovych work for Ukrainian history preservation.Based on problem-chronological method of analysis of Olena Apanovych’s diaries, archive materials of Ukrainian community on memory preservation, personal archive documents, her involvement into social activities of the Soviet and post-Soviet time had been revealed. Prosopographical method allowed us to show the peculiarities of Olena Opanovych relationship with the scientific community.The article described that preservation process started in 1950s when Olena Apanovych, as a member of scientific expedition, researched on remains of Zaporizka Sich. At that time she analyzed the extent of cultural self-awareness as well as the research engaged more interest to the Ukrainian history. Later, in 1950s–1970s Olena Apanovych became one of the major expert of cossacks history preservation in Ukraine, among others, she established the memorial on island Khortytsia. Besides publishing activity on the topic, she led two scientific expeditions “Zaporizka Sich: destroyed and survived”.